The Construction of the Society of Good Living in Times of Globalization - Soledispa Toro, Julieta Magaly (2022)
Good living is more than a way of life of Andean peoples: it is a philosophy, a cosmovision and a form of resistance to the Western model, but they are not the only communities that find answers to daily and social problems and to the manifestations of nature in their millenary wisdom. On the other hand, globalization is the main tool of consumerism that demands unnecessary products, which require the irrational use of natural resources. Consumerism originates waste and squandering. In the throwaway culture, everything ends up in the trash: in the earth or in the oceans. Thus, globalization is at odds with good living, which has as its most important principle: the care of nature. This relationship between globalization and good living, can be redirected for a rapprochement between native cultures and a joint action in an attempt to improve the relationship of human beings with nature. It can also be the platform that makes viable the popular and solidarity economy of good living based on the fair exchange of products. Globalization can be a channel for common actions.